Mastering the Nikon D750 - Young, Darrell, 1958- (Rocky Nook, 2015)
Mastering the Nikon D750 by Darrell Young provides a wealth of experience-based information and insights for owners of the new D750 camera. Darrell is determined to help the user navigate past the confusion that often comes with complex and powerful professional camera equipment. This book explores the features and capabilities of the camera in a way that far surpasses the user's manual. It guides readers through the camera features with step-by-step setting adjustments; color illustrations; and detailed how, when, and why explanations for each option. Every button, dial, switch, and menu configuration setting is explored in a user-friendly manner, with suggestions for setup according to various shooting styles. Darrell's friendly and informative writing style allows readers to easily follow directions while feeling as if a friend dropped in to share his knowledge. The information in this book goes beyond the camera itself and also covers basic photography technique.